Antibacterial Mechanism of Action of Two Types of Honey against Escherichia coli through Interfering with Bacterial Membrane Permeability, Inhibiting Proteins, and Inducing Bacterial DNA Damage - Asma Mohammed Al-Sayaghi; Abdelkodose Mohammed Al-Kabsi; Maisa Siddiq Abduh; Sultan Ayesh Mohammed Saghir; Mohammed Abdullah Alshawsh (MDPI AG, 2022)
Honey is a sweet natural food produced by bees from flower nectar or some part of plant secretions that exhibit antimicrobial activity against many microorganisms. It has been used as traditional therapy for skin infections. Antibiotics play an essential role in managing wound infection; however, some pathogenic bacteria have begun to possess resistance against them, which may cause chronic infections and severe adverse effects. This study investigates the antibacterial activities and mechanism of action of Yemeni Sidr honey (SH) and Manuka honey (MH) against Escherichia coli. The inhibitory effects of SH and MH using the disk diffusion method on bacterial growth were remarkable at 700 mg/disk. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were similar for both kinds of honey. However, MH showed a better bactericidal effect (30%) than SH (50%). The antimicrobial mechanism of action showed that SH substantially impacted the bacterial membrane's permeability and increased the potassium and protein leakage rate. On the contrary, MH demonstrated remarkable inhibition of bacterial protein synthesis, while both kinds of honey caused bacterial DNA damage. These data reveal that SH and MH could be used as a remedy for skin infections and might be further developed as a promising dressing for bacterial wound infections.